Local Wisdom 'Sumbang Duo Baleh' Its Role in Shaping the Religious Character of Elementary School Students - Wahyuni, Resti; Samad, Duski; Zalnur, Muhammad (International Journal of Islamic Studies Higher Education, 2025)
Religious character is an important dimension in basic education that aims to shape students to be faithful, pious, and have noble character in accordance with the values of Islamic teachings. This study aims to analyze the role of local wisdom Sumbang Duo Baleh in shaping the religious character of elementary school students. Sumbang Duo Baleh is twelve Minangkabau customary prohibitions rooted in the philosophy of Adat Basandi Syarak, Syarak Basandi Kitabullah. The study was conducted at elementary school, which integrates local Minangkabau content into the curriculum. The research method used a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that although there are still obstacles in the form of limited teaching materials and differences in the level of teacher understanding, the implementation of Sumbang Duo Baleh contributes significantly to strengthening students' religious character. The values instilled include behavior that respects others, maintains politeness in dress and speech, and fosters awareness of personal responsibility before Allah SWT. This integration of local wisdom also fosters positive habits in students' daily lives, such as disciplined worship, polite speech, and avoiding reprehensible behavior. These findings confirm that the use of Sumbang Duo Baleh as local content is relevant and effective in supporting the development of students' religious character while simultaneously strengthening Minangkabau cultural identity amidst the currents of modern education.